Virtual Sensory Feedback for Gait Improvement in Neurological Patients - Baram, Yoram (Frontiers in Neurology, 2013)
We review a treatment modality for movement disorders by sensory feedback. The natural closed-loop sensory-motor feedback system is imitated by a wearable virtual reality apparatus, employing body-mounted inertial sensors and responding dynamically to the patient’s own motion. Clinical trials have shown a significant gait improvement in patients with Parkinson's disease using the apparatus. In contrast to open-loop devices, which impose constant-velocity visual cues in a “treadmill” fashion, or rhythmic auditory cues in a “metronome” fashion, requiring constant vigilance and attention strategies, and in some cases, instigating freezing in Parkinson’s patients, the closed-loop device improved gait parameters and eliminated freezing in most patients, without side effects. Patients with multiple sclerosis, previous stroke, senile gait and cerebral palsy using the device also improved their balance and gait substantially. Training with the device has produced a residual improvement, suggesting virtual sensory feedback for the treatment of neurological movement disorders.